2012
DOI: 10.1016/j.seizure.2012.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Stevens–Johnson syndrome induced by levetiracetam

Abstract: The Stevens-Johnson syndrome (SJS) is a life-threatening skin condition caused by a hypersensitivity complex, which affects the skin and the mucous membranes. This syndrome is closely related to the application of antiepileptic drugs (AEDs). 1 Most cases are caused by aromatic AEDs, such as phenytoin, carbamazepine, oxcarbazepine, phenobarbital, lamotrigine, and other aromatic drugs. 2 Levetiracetam (LEV), the S-enantiomer of a-ethyl-2-oxo-1- DiscussionAntiepileptic drug hypersensitivity syndrome (AHS) is a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 12 publications
(13 reference statements)
0
15
0
Order By: Relevance
“…24,1015 In a systematic review of ten randomised controlled trials by Mbizvo et al, adverse effect profile of LEV in patients of drug-resistant epilepsy was studied, and rash due to LEV was reported in only two studies. It was noted that only symptoms affecting more than 5 or 10% of participants of the groups were published in these ten trials 16.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,1015 In a systematic review of ten randomised controlled trials by Mbizvo et al, adverse effect profile of LEV in patients of drug-resistant epilepsy was studied, and rash due to LEV was reported in only two studies. It was noted that only symptoms affecting more than 5 or 10% of participants of the groups were published in these ten trials 16.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Sharma et al, out of 500 patients with cADRs with all drugs, anticonvulsants - PHT, CBZ and PB were implicated in 41.6% of patients with maculopapular rashes and 43.8% of life-threatening reactions - TEN and SJS 1. Although non-aromatic AEDs like Topiramate (TPM) and LEV are thought to be safer, there are several reports of even severe cADRs like SJS, DRESS due to LEV 24. In 2011, the United States Food and Drug Administration (US-FDA) included serious cADRs as potential safety risk from LEV in both paediatric and adult population 5…”
Section: Introductionmentioning
confidence: 99%
“…Many studies in human and veterinary medicine have shown that IV levetiracetam does not cause serious adverse events when administered over a period less than 15 minutes, or when administered in a more concentrated form than that which is recommended on the label . Rare cases of serious adverse events have, however, been reported in the human literature …”
Section: Discussionmentioning
confidence: 99%
“…Intravenous LEV use may be increased in the future. There are some reported side effects including Steven Johnson syndrome, bullous pemphigoid, and aggravation of myoclonus and non-convulsive SE (Isoda et al, 2012;Karadag et al, 2012;Liu et al, 2012;Zou et al, 2012). Rare conditions such as hypersexuality are also reported after LEV use (Metin et al, 2012).…”
Section: Discussionmentioning
confidence: 99%